“BIDANKUPEDIA” SEBAGAI MEDIA E-HEALTH KONSULTASI TENTANG KESEHATAN REPRODUKSI DAN PERMASALAHANNYA - Nur Maziyah Hurin'in; Fedelita Aistania Putri; Prastiwi Novia Puspitasari (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Health services such as health education or online questions and answers, especially during a Covid-19 pandemic, can use telehealth. This community service was to provide education and consultation on questions and answers about reproductive health. The method used in this community service activity is innovation and modification of consulting services, questions and answers such as midwifery questions and answers which are usually carried out directly, as an effort to bring midwifery services closer to the community in the form of online question and answer consultations using Google Form media as the initial registration medium. then followed by electronic messages using WhatsApp media as a follow-up media for the question and answer consultations. The community service result showed that almost half of the respondents (42.8%) asked about the topic of reproductive health about infertility. All respondents (100%) answered the questionnaire satisfied with the educational answers from the organizers. Independent practice midwives can use e-health solutions for solutions to overcome patient queues and make an initial agreement before meeting face to face for follow-up examinations, the e-health program can also be a superior service program from independent midwife practices.